Mandibular reconstruction with free non-vascularized rib autograft - N. G. Barannik; O. O. Mosieyko; O. M. Manukhina; A. V. Sidoryako (Сучасні медичні технології)
Purpose of the study. To increase the effectiveness of rehabilitation of patients with acquired bone defects of the mandible with the help of rib free non-vascularized autografts.